The novel approach for realizing carbon neutrality of coal: backfill material-assisted CO2 sequestration in UCG combustion cavities - Lin Xin; Lingran Min; Min Yang; Shuqin Liu; Weimin Cheng; Maofei Niu; Ruonan Wang; Tongtong Diao (Fuel, 2026)

Molecular bridging stabilizes halide perovskites for durable photocatalytic H2 production in pure water - Xiwen Ma; Na Han; Wanying Cheng; Guiqiang Diao; Ming Sun; Shaomin Peng; Guichuan Xing; Lin Yu (Chemical Engineering Journal, 2026)

Individual and combined exposures to polystyrene nanoplastics and benzophenone-3 induce developmental, behavioral and transcriptomic impairments in marine larval clownfish (Amphiprion frenatus) - Yankun Zhang; Fang Lin; Shaobai Wen; Muhammad Junaid; Han Qian; Xiaoping Diao (Marine Pollution Bulletin, 2026)

Dynamic disruption of interfacial hydrogen-bond networks via orbital engineering for accelerated alkaline hydrogen evolution - Juping Wang; Hongyue Diao; Zexing Wu; Weiping Xiao; Qi Wu; Tianyi Ma; Nan Lin; Haibo Lin; Lei Wang (Chemical Engineering Journal, 2026)

Complete Mitochondrial Genome of Turrum coeruleopinnatum Provides Phylogenetic Context and Candidate Selection Signals Within Carangidae - Yang Chen; Xuehui Diao; Yixuan Lin; Jinghua Wu; Ruling Wei (Biochemical Genetics, 2026)

How the built environment shapes the spatiotemporal imbalances in dockless bike-sharing usage: A network-based analysis of Shenzhen, China - Zijun Wei; Keyu Lin; Mi Diao (Applied Geography, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Aging enhances the ecological toxicity of polyethylene microplastics to marine medaka larvae (Oryzias melastigma) - Shaobai Wen; Jin Liu; Bigui Lin; Na Li; Xiaoping Diao (Journal of Environmental Management, 2026)

Structurally diverse sesquiterpenoid glycosides with anti-inflammatory activity from Cissampelopsis spelaeicola - Si-Hang Lin; Ning Diao; Yan Wang; Dong Liang (Phytochemistry, 2026)

Adaptive multi-objective optimization of thermal and perceptual livability in high-density residential environments using image-based spatial metrics - Xudong Zhang; Weiyi Jia; Haifeng Diao; Taihan Chen; Ziyuan Zhang; Ervine Shengwei Lin; Zhiqiang Wu (Building and Environment, 2026)

Radial wettability gradient core-shell fiber design enables synergistic solar reflection and moisture-driven cooling - Baichun Long; Bingxin Sun; Liwei Lin; Yuxuan Jiang; Zhaoning Yang; Guowang Diao; Dianchen Feng; Yuanzhe Piao; Wang Zhang (Chemical Engineering Journal, 2026)

The flavor properties of Amadori rearrangement products and their potentials in flavor replication of plant-based meat analogs: a review - Huan Zhan; Wenjing Xin; Yang Deng; Tao Lin; Qingshan Shen; Khizar Hayat; Yanli Ma; Yuduan Diao (Critical Reviews in Food Science and Nutrition, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Anomalous transport of colloidal goethite and plutonium in single granite fracture experiments: Modeling and evaluation - Dong-Xu Liu; Qi Cheng; Hao Diao; Liu-Xing Huang; Zeng-Hu Ma; Jian-Feng Lin (Journal of Hydrology, 2025)

UPRS-1: A regolith simulant of Utopia Planitia, Mars - Yiming Diao; Honglei Lin; Juan Li; Shouding Li; Changyi Xu; Zhaobin Zhang; Zongyu Yue; Bo Zheng; Xiukuo Sun; Tao Xu; Xinshuo Chen; Yanfang Wu; et al. (Icarus, 2025)

Constructing phase interface in membranes of ultralong layered VxOy nanobelts for exceptional EMI shielding, thermal management, waterproofing, and strain sensing applications - Siyu Xie; Kang Fu; Qian Lin; Ziyi Wu; Junhao Diao; Sirun Yu; Shuhan Huang; Liyan Xie; Guoxiu Tong (Chemical Engineering Journal, 2025)

A small amount of Pd promotes CO2 adsorption and reduces carbon deposition to double the stability of NiFePd/MgAlO catalyst for plasma-assisted dry reforming reaction - Lian-He Zhao; Shu-Juan Lin; Jian-Feng Diao; Ming-Sheng Wang; Jing Sun; Zhong-Ning Xu; Guo-Cong Guo (Chemical Engineering Journal, 2025)

Does bike-sharing support the development of 15-minute cities? A case study of Zhejiang Province, China - Yongping Zhang; Wenyan Fu; Hui Kong; Diao Lin (Sustainable Cities and Society, 2025)

Synergistic separation of imprinted composite membranes: Combining a porous graphene oxide skeleton with continuous MOFs nanolayers for superior selective separation - Yilin Wu; Hang Cui; Jiaqing Zhang; Chao Zhou; Rongxin Lin; Zequan Diao; Ming Yan (Desalination, 2025)

Seasonal characteristics, source apportionment and ecological risk assessment of priority and emerging contaminants using passive samplers in the coastal water - Zishan Diao; Xianyin Ping; Xue Zhang; Bin Hui; Fanping Zhu; Yiqiao Zhang; Jing Wang; Yinjie Yu; Lin Zhang; Wenjia Hui; Xiaomin Xie; Xiaohan Zhang; et al. (Journal of Hazardous Materials, 2025)

Cytokine profiling in COVID-19 patients by using ion mobility-mass spectrometry-based parallel reaction monitoring - Ling Yan; Chenrui Yuan; Runhou Zhou; Li Zhong; Kelvin Kai-Wang To; Na Liu; Xin Diao; Guangshan Xie; Hongzhi Zhao; Haijiang Wu; Lin Zhu; Zhiwei Chen; et al. (Analytica Chimica Acta, 2025)

Delivery of NK cells in an injectable dynamic hydrogel effectively remodels tumor microenvironment and inhibits post-surgery tumor recurrence - Jiaying Long; Yicong Zhang; Mengxing Zhang; Zhenkang Diao; Taotian Zhang; Hanming Zhang; Qing Lin; Tao Gong; Xun Sun; Zhirong Zhang; Shiqi Huang; Ling Zhang (Chemical Engineering Journal, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Sedimentary geochemical records of the palaeovegetation and palaeoclimate evolution in the Pinghu Formation, Western Slope Belt, Xihu Sag, East China Sea Basin - Yanan Wang; Lin Wei; Xiong Cheng; Hui Diao; Wenjun Li; Dujie Hou; Jiansheng Li (Organic Geochemistry, 2025)

Exploring the use of bacillomycin D to control citrus sour rot caused by Geotrichum citri-aurantii - Shiquan Qian; Xinrong Zhou; Lin lv; Qi Sun; Xinran Cheng; Qian Xie; Yanrui Chai; Enjie Diao (Journal of Stored Products Research, 2025)

Surgical treatment of Meniere’s disease - Yixu Wang; Hongwei Zheng; Xin Ma; Lin Han; Tongxiang Diao; Lisheng Yu; Maoli Duan (Science Bulletin, 2025)

Degradation of ofloxacin by activation of persulfate with metal-N co-doped modified peanut shell biochar: The key role of cobalt doping - Wei Qian; Yi-Li Deng; Xiao-Long Liu; Hui Liu; Mao-You Ye; Ying-Ying Li; Yong-Zheng Zhang; Zeng-Hui Diao; Jia-Lin Liang (Journal of Water Process Engineering, 2025)

Relationship between shared micromobility and public transit: The differences between shared bikes and shared E-bikes - Hui Kong; Hao Chao; Wenyan Fu; Diao Lin; Yongping Zhang (Journal of Transport Geography, 2025)

National scale sub-meter mangrove mapping using an augmented border training sample method - Jinyan Tian; Le Wang; Chunyuan Diao; Yameng Zhang; Mingming Jia; Lin Zhu; Meng Xu; Xiaojuan Li; Huili Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Engineering isolated cationic vacancies on nickel–iron layered double hydroxides for efficient oxygen evolution reaction - Qiulu Gao; Chao Lin; Zheng Lin; Xiaopeng Liu; Qianfan Zhang; Peng Diao (Chemical Engineering Journal, 2025)

Blocking the PD-1 signal transduction by occupying the phosphorylated ITSM recognition site of SHP-2 - Wenjie Li; Wenyi Mei; Hewei Jiang; Jie Wang; Xiaoli Li; Lina Quan; Yanyan Diao; Yanni Ma; Sisi Fan; Zhuwei Xie; Mengdie Gong; Huan Zhu; et al. (Science China Life Sciences, 2025)

Impacts of new metro lines on the activity space of older people - Mi Diao; Keyu Lin; Zheng Chang (Transportation Research Part D: Transport and Environment, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Lactococcus lactis subsp. lactis LJL7m20 strongly inhibits growth of the Bacillus cereus group from sufu - Jialu Xian; Huifang Wang; Siying Diao; Nan Zhang; Sisi Lin; Rui Zhang; Zekun Jin; Zhaohui Zhou; Liling Lu; Sameh A. Korma; Li Li (Food Bioscience, 2024)

Recombinant avian-derived antiviral proteins cIFITM1, cIFITM3, and cViperin as effective adjuvants in inactivated H9N2 subtype avian influenza vaccines - Shihong Yan; Yikai Chen; Jin Lin; Huimin Chen; Chenqi Hu; Hongyang Liu; Hongxiu Diao; Shasha Liu; Ji-Long Chen (Veterinary Microbiology, 2024)

Supramolecular modified porous carbons with hierarchical adsorption of quinone active molecules for high performance supercapacitors - Xusen Li; Xiyun Wang; Bingxin Sun; Ting Chen; Yuanzhe Piao; Guowang Diao; Liwei Lin; Wang Zhang (Chemical Engineering Journal, 2024)

Mechanically customizable lignin bio-elastomers based on tailorable multiscale microstructures - Dengfeng Wang; Mengyuan Diao; Yaotao Shan; Han Wu; Lin Liu; Zihan Li; Haojie Hong; Juming Yao (Chemical Engineering Journal, 2024)

Rac1 promotes the lipopolysaccharide-induced inflammatory response and contraction-associated proteins (CAPs) expression in mouse uterine smooth muscle cells - Min Diao; Yunkai Tao; Qian Liu; Lu Huang; Hao Li; Xuemei Lin (Reproductive Biology, 2024)

Nitrogen aerosols in New Delhi, India: Speciation, formation, and sources - Qiaomin Pei; Xin Wan; David Widory; Kirpa Ram; Bhupesh Adhikary; Guangming Wu; Xing Diao; Hemraj Bhattarai; Yan-Lin Zhang; Mark Loewen; Zhiyuan Cong (Atmospheric Research, 2024)

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

Removal of pesticide acetamiprid using KOH activated biochar derived from crayfish shell: Behavior and mechanism - Xiao-Wen Yao; Xie Chen; Man-Li Chen; Neng-Jia Feng; Lin-Yin Tong; Yun-Qiang Yi; Wei Qian; Zeng-Hui Diao (Process Safety and Environmental Protection, 2024)

Multi-omics analysis of attenuated variant reveals potential evaluation marker of host damaging for SARS-CoV-2 variants - Guangshan Xie; Lin Zhu; Siwen Liu; Cun Li; Xin Diao; Yanhao Zhang; Xiuli Su; Yuanyuan Song; Guodong Cao; Li Zhong; Pui Wang; Xiaojuan Liu; et al. (Science China Life Sciences, 2024)

Effects of deposition height stability of CuCrZr alloy based on arc voltage sensing: Influence of materials and energy saving on wire arc additive manufacturing - Zhaowei Diao; Fei Yang; Lin Chen; Rui Wang; Yang Zhang; Jinru Sun; Yifei Wu; Mingzhe Rong (Journal of Cleaner Production, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Exploring plausible contributions of end-use harvested wood products to store atmospheric carbon in China - Jianheng Zhao; Xinyuan Wei; Jiaojiao Diao; Hua Chen; Shiran Lin; Zehui Zhu; Xiangyu Jiang; He Zhu (Biomass and Bioenergy, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

Heterogeneous aggregation between microplastics and microalgae: May provide new insights for microplastics removal - Yuanyuan Su; Liu Gao; Licheng Peng; Xiaoping Diao; Shengyou Lin; Ruiqi Bao; Tariq Mehmood (Aquatic Toxicology, 2023)

Legacy and novel perfluoroalkyl substances in major economic species of invertebrates in South China Sea: Health implication from consumption - Jieyi Diao; Zhenwei Chen; Chuanghong Su; Jianwen Wang; Zhixin Zheng; Qiongping Sun; Lin Wang; Ran Bi; Tieyu Wang (Marine Pollution Bulletin, 2023)

A green synthesized medicine residue carbon-based iron composite for the removal of chromium (VI) and cadmium (II): Performance, kinetics and mechanism - Fa-Ming Diao; Man-Li Chen; Lin-Yin Tong; Ying-Nan Chen; Zeng-Hui Diao (Environmental Science and Pollution Research, 2023)

The impact analysis of media attention on local environmental governance based on four-party evolutionary game - Feng Pan; Zexin Diao; Lin Wang (Ecological Modelling, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Occurrenceand characteristics of microplastics in benthic species from mangrove wetlands of Hainan, South China - Qinzhou Zhang; Jia Xie; Siyuan Ma; Yingya Chen; Fang Lin; Xiaoping Diao (Frontiers in Marine Science, 2023)
Microplastics (MPs) are emerging contaminants that pose a global threat to the environment. Mangrove ecosystems, which contribute to biogeochemical cycles, are vulnerable to various anthropogenic disturbances and chemical pollutants. In this study, the abundance and the characteristics of MPs were investigated in 10 species of benthic organisms, including crabs, bivalves, and snails, from seven typical mangrove distribution areas, with a total of 15 sampling sites in Hainan, South China. The abundance of MPs in each sampling site ranged between 0.83 ± 1.32 and 12.00 ± 0.00 items/individual, with an average of 3.90 ± 3.31 items/individual, while the abundance of MPs varied between 0.17 and 2.00 items/individual for the different species. Fibers (80.13%) were the most abundant MPs, most of the MPs were brown (37.18%) or blue (26.64%), and more than 80% were small-sized plastic (<2 mm). Raman analysis showed that polypropylene (94.44%) was the most dominant type of polymer. In addition, crabs (with an average abundance of 1.10 ± 0.59 items/individual) showed a higher potential for accumulating MPs than the other species investigated in the present study. This study shows that MPs are widely distributed throughout benthic species in the mangrove wetlands of Hainan.

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

A field study of nano-FeS loaded lignin hydrogel application for Cd reduction, nutrient enhancement, and microbiological shift in a polluted paddy soil - Xiujiao Wei; Huayi Chen; Diao Lin; Huijuan Xu; Jinjin Wang; Jiaxin Zhang; Zheng Hu; Jianbin Deng; JianPeng Gao; Hanhao Li; Yongtao Li; Yonglin Liu; et al. (Chemical Engineering Journal, 2023)

Lipid Microparticles Show Similar Efficacy With Lipid Nanoparticles in Delivering mRNA and Preventing Cancer - Afang Ji; Minghao Xu; Yunzhi Pan; Lu Diao; Lin Ma; Li Qian; Junping Cheng; Mi Liu (Pharmaceutical Research, 2023)

A review on the removal of phthalate acid esters in wastewater treatment plants: from the conventional wastewater treatment to combined processes - Lin Bai; Xiaowan Dong; Fangshu Wang; Xiaohan Ding; Zhikai Diao; Dong Chen (Environmental Science and Pollution Research, 2022)

Community Structure of Benthic Macrofauna and the Ecological Quality of Mangrove Wetlands in Hainan, China - Ping Li; Jingli Liu; Jiankun Bai; Yifan Tong; Yuchen Meng; Xiaoping Diao; Ke Pan; Xiaoshan Zhu; Guanghui Lin (Frontiers in Marine Science, 2022)
Few studies have systematically assessed the ecological status of mangrove wetlands following the stress of anthropogenic activities in China. This study investigated the spatial and seasonal distribution of benthic macroinvertebrate communities and assessed the ecological quality of mangrove habitats on an island scale in Hainan, China (containing the third largest mangrove area of China and the highest mangrove species richness). For the benthic macrofauna community structure, a total of 102 macrobenthic taxa belonging to 50 families were identified, with Crustaceans, Molluscs, Polychaetes, and Oligochaeta having relative abundances of 52.3%, 36.1%, 10.8%, and 0.8%, respectively. Decapoda and Gastropoda dominated the benthic community abundance. Non-metric multidimensional scaling and an analysis of similarities revealed significantly different macroinvertebrate assemblages among the regions during the two seasons. The South mangroves had the lowest macrofauna species numbers, biodiversity, richness, and abundance. The macrofaunal species richness, Shannon index, Margalef index, abundance, and biomass markedly affected by region and season. As indicated by the biotic indices AMBI (AZTI’s Marine Biotic Index) and M-AMBI, more than half of the mangrove habitats on Hainan Island were slightly to heavily disturbed and had poor to moderate ecological quality. Our results recommend long-term monitoring for evaluating the quality status of mangrove wetlands and avoiding extensive land-use conversion of mangroves. Holistic approaches considering ecological characteristics and combining information on both floral and faunal functionality would contribute to the effective management and conservation of mangroves in disturbed areas.

Hemorrhage-Induced Sphingosine Kinase 1 Contributes to Ferroptosis-Mediated Secondary Brain Injury in Intracerebral Hemorrhage - Xiaojun Diao; Qi Cui; Ning Tian; Zixian Zhou; Wenjing Xiang; Yanlin Jiang; Jungang Deng; Hongzhan Liao; Xiaohui Lin; Qinghua Li; Rujia Liao (Molecular Neurobiology, 2022)

Video target detection of East Asian migratory locust based on the MOG2-YOLOv4 network - Zhao Bai; Zhan Tang; Lei Diao; Shuhan Lu; Xuchao Guo; Han Zhou; Chengqi Liu; Lin li (International Journal of Tropical Insect Science, 2022)

Molecular cloning and characterization of five genes from embryogenic callus in Miscanthus lutarioriparius - Lingling Zhao; Xiaofei Zeng; Xiaohu Hu; Jiajing Sheng; Fenglin Zhu; Lin Zhong; Fasong Zhou; Surong Jin; Zhongli Hu; Ying Diao (Acta Physiologiae Plantarum, 2020)
The regeneration from embryogenic callus of higher plants in tissue culture is regulated by explants types and developmental stage and also regulated by some genes. In Miscanthus lutarioriparius , five candidate genes were selected to decide the differential expression between embryogenic and non-embryogenic calli, including MlARF-GEP (guanine nucleotide-exchange protein of ADP ribosylation factor), MlKHCP (kinesin heavy chain like protein), MlSERK1 (somatic embryogenesis receptor-like kinases 1), MlSERK2 (somatic embryogenesis reportor-like kinases 2), and MlTypA (tyrosine phosphorylation protein A) with Genbank accession numbers KU640196–KU640200. Multiple sequence alignment analysis showed that five genes were highly conserved among members of their gene families respectively. Phylogenetic relationship analysis showed that five genes were closest with homologous genes of Zea mays and Sorghum . The qRT-PCR results showed significant differences of five genes expression pattern between two different callus types, the relative expression in embryogenic callus was detected to exceed in non-embryogenic callus. Furthermore, simple sequence repeats (SSR) marker statistics results via Chi-square showed a significant correlation between MlSERK1 genotype and induction of embryogenic callus in M. lutarioriparius . This study may lay the foundation of the molecular mechanism on the embryogenic callus induction of M. lutarioriparius and perhaps provide some gist for further study on genetic manipulation.

Applying Iterative Method to Solving High-Order Terms of Seafloor Topography - Diao Fan; Shanshan Li; Shuyu Meng; Yi Lin; Zhibin Xing; Chi Zhang; Junjun Yang; Xiaoyun Wan; Zhenhao Qu (Marine Geodesy, 2020)

Effects of resveratrol on regulation on UCP2 and cardiac function in diabetic rats - Jiayu Diao; Jin Wei; Rui Yan; Gang Fan; Lin Lin; Mengjie Chen (Journal of Physiology and Biochemistry, 2019)

Spatial relationship between climatic diversity and biodiversity conservation value - Junjun Wang; Ruidong Wu; Daming He; Feiling Yang; Peijun Hu; Shiwei Lin; Wei Wu; Yixin Diao; Yang Guo (Conservation Biology, 2018)
Capturing the full range of climatic diversity in a reserve network is expected to improve the resilience of biodiversity to climate change. Therefore, a study on systematic conservation planning for climatic diversity that explicitly or implicitly hypothesizes that regions with higher climatic diversity support greater biodiversity is needed. However, little is known about the extent and generality of this hypothesis. We used the case of Yunnan, southwest China, to quantitatively classify climatic units and modeled 4 climatic diversity indicators, including the variety (VCU), rarity (RCU), endemism (ECU) of climatic units, and a composite index of climatic diversity (CICD). We used 5 schemes that reliably identify priority conservation areas (PCAs) to identify areas with high biodiversity conservation value. We then investigated the spatial relationships between the 4 climatic diversity indicators and the results of the 5 PCA schemes and assessed the representation of climatic diversity within the existing nature reserves. The CICD was the best indicator of areas with high conservation value, followed by ECU and RCU. Contrary to conventional knowledge, VCU was not positively associated with biodiversity conservation value. The rarer or more endemic climatic units tended to have higher reserve coverage than the more common units. However, only 28 units, covering 10.5% of the land in Yunnan, had >17% of their areas protected. In addition to climatic factors, topography and human disturbances also significantly affected the relationship between climatic diversity and biodiversity conservation value. Our results suggest that climatic diversity can be an effective surrogate for establishing a more robust reserve network under climate change in Yunnan. Our study improves understanding of the relationship between climatic diversity and biodiversity and helps build an evidence‐based foundation for systematic conservation planning that targets climatic diversity in response to climate change.

Experimental Investigation About Influence of Pre-existing Fracture on Hydraulic Fracture Propagation Under Tri-axial Stresses - Wan Cheng; Yan Jin; Qing Lin; Mian Chen; Yakun Zhang; Ce Diao; Bing Hou (Geotechnical and Geological Engineering, 2015)

Adenosylmethionine Decarboxylase 1 (AMD1)-Mediated mRNA Processing and Cell Adhesion Activated & Inhibited Transition Mechanisms by Different Comparisons Between Chimpanzee and Human Left Hemisphere - Lin Wang; Juxiang Huang; Minghu Jiang; Haizhen Diao; Huilei Zhou; Xiaohe Li; Qingchun Chen; Zhenfu Jiang; Haitao Feng (Cell Biochemistry and Biophysics, 2014)

A prospective clinical study in hepatitis B e antigen-negative chronic hepatitis B patients with stringent cessation criteria for adefovir - Minghao Ha; Guotong Zhang; Shu Diao; Mingfang Lin; Liping Sun; Huiyuan She; Chenbao Kuan; Lihui Shen; Chunhong Huang; Wenjuan Shen; Zhongming Huang (Archives of Virology, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

Expression patterns of prion protein gene in differential genotypes sheep: quantification using molecular beacon real-time RT-PCR - Chuan Wang; Run Wu; Fa-Di Li; Lei Liu; Xiao-Li Zhang; Chun-Lin Zhao; Xiao-Long Diao; Hong-Wei Guan (Virus Genes, 2011)